2017
DOI: 10.3747/co.24.3648
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Pan-Canadian Oncology Drug Review on Provincial Concordance with Respect to Cancer Drug Funding Decisions and Time to Funding

Abstract: BackgroundThe pan-Canadian Oncology Drug Review (pcodr) was implemented in 2011 to address uneven drug

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The pCODR process was implemented in 2011 by the Ministries of Health (except Quebec), replacing the interim Joint Oncology Drug Review , with the goal of informing provincial reimbursement decisions based on clinical efficacy and cost‐effectiveness . Although previous research suggests that pCODR improved the median time from Health Canada approval to public funding from 522 to 393 days , the median time required for the HTA was 141 days (range 112–282) and only 50% met the target of 140 days . In our present analysis, the median time for the pCODR HTA was longer, at close to 9 months.…”
Section: Discussionmentioning
confidence: 99%
“…The pCODR process was implemented in 2011 by the Ministries of Health (except Quebec), replacing the interim Joint Oncology Drug Review , with the goal of informing provincial reimbursement decisions based on clinical efficacy and cost‐effectiveness . Although previous research suggests that pCODR improved the median time from Health Canada approval to public funding from 522 to 393 days , the median time required for the HTA was 141 days (range 112–282) and only 50% met the target of 140 days . In our present analysis, the median time for the pCODR HTA was longer, at close to 9 months.…”
Section: Discussionmentioning
confidence: 99%
“…However, it also reflects differences between countries in the time taken to complete coverage and pricing processes, where relevant. 43 Both medicines were already approved in other indications. 44 https://www.fda.gov/about-fda/oncology-center-excellence/project-orbis; https://www.tga.gov.au/media-release/provisionalapplication-receives-approval-through-first-international-collaborative-review-initiative-between-tga-fda-and-hc, consulted on 18 March 2020 45 Time to access could not be computed for a number of countries that did not provide the necessary information, including Australia, Chile, Germany, Lithuania, and the United States.…”
Section: Time From First Country Marketing Approval To Coverage In a mentioning
confidence: 99%
“…Once market exclusivity is exhausted, competition from generics or biosimilars is expected to result in lower prices and cost savings. Usually, the price difference between originator and generic is higher than that between originator and biosimilar (up to 80% versus 15-30%, respectively) (Simoens, 2011 [43]; Nabhan et al, 2018 [44]). However, potential savings are high given that biologic prices are generally higher than small molecules and that the market share of biologics is increasing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In an article appearing in this issue of Current Oncology, Srikanthan et al 6 examine the effect of the pcodr on ttl (that is, the time from a noc being issued to drug funding) and provincial decision concordance. Using the Health Canada Drug Product Database, the investigators identified 88 new indications for cancer drugs (representing 51 unique cancer drugs) between January 2003 and May 2014, and they researched relevant drug funding dates and decisions in provincial formulary listings.…”
mentioning
confidence: 99%